Pseudomonas koreensis Recovered From Raw Yak Milk Synthesizes a β-Carboline Derivative With Antimicrobial Properties - Kaur, Manpreet; Jangra, Manoj; Singh, Harjodh; Tambat, Rushikesh; Singh, Nittu; Jachak, Sanjay M.; Mishra, Sunita; Sharma, Charu; Nandanwar, Hemraj; Pinnaka, Anil Kumar (Frontiers in Microbiology, 2019)
Natural evolution in microbes exposed to antibiotics causes inevitable selection of resistant mutants. This turns out to be a vicious cycle which requires the continuous discovery of new and effective antibiotics. For the last six decades, we have been relying on semisynthetic derivatives of natural products discovered in ‘Golden Era’ from microbes, especially Streptomyces sp. Low success rates of rational drug-design sparked a resurgence in the invention of novel natural products or scaffolds from untapped or uncommon microbial niches. Therefore, in this study, we examined the microbial diversity inhabiting the yak milk for their ability to produce antimicrobial compounds. We prepared the crude fermentation extracts of fifty isolates from yak milk and screened them against indicator strains for the inhibitory activity. Later, with the aid of gel filtration chromatography followed by reversed-phase HPLC, we isolated one antimicrobial compound Y5-P1 from the strain Y5 (Pseudomonas koreensis) which showed bioactivity against Gram-positive and Gram-negative bacteria. The compound was chemically characterized using HRMS, FTIR and NMR spectroscopy and identified as 1-acetyl-9H-β-carboline-3-carboxylic acid. It showed minimum inhibitory activity (MIC) in the range of 62.5–250 µg /ml. The cytotoxicity results revealed that IC50 against two mammalian cell lines i.e. HepG2 and HEK293T was 500µg/ml and 750µg/ml respectively. This is the first report on the production of this derivative of β-carboline by the microorganism. Also, the study enlightens the importance of microbes residing in uncommon environments or unexplored habitats in the discovery of a diverse array of natural products which could be designed further as drug candidates against highly resistant pathogens.